Pemodelan Sistem Antrian Multiserver di Kantor Samsat Kota Padang berdasarkan Aspiration Level - Putri, Anisa Dianda; Rosha, Media (UNIVERSITAS NEGERI PADANG, 2024)
Queues in everyday life are very common. Situations like this are often found in public service facilities, one of which is the Padang City SAMSAT Office. The research objective was tovdetermine the optimal queuing system model based on the aspiration level. This researchvisvan applied research withvprimary datavtypes. Thevdata analysisvtechnique usedvisvcalculating the average time between arrivals and the average service time, testing the suitability of the distribution with the Kolmogorov Smirnov test, then analyzed using the queuing model. The results showed that based on the aspiration level, the optimal queuing system model on Mondays, Wednesdays, Thursdays and Fridays at the Padang City SAMSAT Office was (M/M/9):(GD/∞/∞). The results of thevaspiration level decisions on Monday, Wednesday, Thursday and Friday with thevadditionvofvthe numbervofvofficersvto 10 people show that the percentage of unemployed officers is 18.5% of their working time and the average time taxpayers wait in the system is approximately 25.58 minutes.